2010
DOI: 10.18202/jamal.2010.12.7101
|View full text |Cite
|
Sign up to set email alerts
|

Studi Fenomenologi Akuntabilitas Non Governmental Organization

Abstract: The purpose of this study is to investigate the phenomenon of accountability in non-governmental organizations (NGOs Pendahuluan Latar belakangBerbagai kritik dalam artikel dan media masa menyoroti akuntabilitas non governmental organization (NGO) 2 semakin berkembang sehubungan isu penyaluran dana

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
0
10
0
8
Order By: Relevance
“…Some empirical studies on financial accountability including intrinsic value, such as carried out by Fikri (2010) on organizations concern on environment, namely WWF ( World Wide for Nature ).The result of the study indicated that WWF has two forms of formal accountability, namely financial accountability and program accountability. In addition, the organization also carries out non-formal accountability, namely action accountability to community.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some empirical studies on financial accountability including intrinsic value, such as carried out by Fikri (2010) on organizations concern on environment, namely WWF ( World Wide for Nature ).The result of the study indicated that WWF has two forms of formal accountability, namely financial accountability and program accountability. In addition, the organization also carries out non-formal accountability, namely action accountability to community.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kajian akuntabilitas yang berbeda dilakukan oleh Fikri et al, (2010) yaitu kajian akuntabilitas pada non-govermental organization. Akuntabilitas pada non-govermental organization (NGO) bukan merupakan sesuatu yang dianggap penting bagi masyarakat.…”
Section: Kajian Teori 21 Akuntabilitasunclassified
“…Accountability can be carried out through various forms, such as written and oral actions or behaviours. Accountability is usually written in the form of formal accountability, while accountability behavioural accountability can be formal or non-formal (Fikri, 2010). To find out how accountability is defined and whether accountability to the mosque congregations is important, the researcher tried to confirm the treasurer and the head of the mosque management:…”
Section: Accountability: Physical Evidence -The Visible Real Workmentioning
confidence: 99%